Effect of different inclusion level of mulberry (Morus Alba) pellet on growth performance and feed conversion ratio of rabbit - Zubaidah Nizar (2022)
The rabbit (Oryctolagus cuniculus) is a commercially farmed agricultural animal. In Malaysia, it was still in its infancy with the biggest challenge confronting the high cost of feeding. Most commercial pellets for rabbits were pricey which make many farmers use other alternative approaches to lower the feeding expenses by offering lucerne and chosen leaves with high protein contained. However, most of the raw lucernes included a high percentage of moisture, leading to diarrhea problems for rabbits if provided directly. The current research encompassed all the processes of producing the mulberry leaves to a fully formed pellet and testing the rabbit in a feed trial. These experiments were undertaken to investigate the efficacy of both kinds of pellets in terms of growth performance, feeding intake, and feed conversion ratio centered on rabbit growth performance. Different diets were allocated into groups, including the control group (100% commercial pellet), treatment 1 (100% mulberry pellet) and treatment 2 (50%mulberry leaf pellet, 50% commercial pellet). Nutritional contents of both pellets were assessed, which include dry matter (DM), moisture, crude protein (CP), crude fat (ether extract), and ash contents. The growth performance measures include average weekly body weight increase, which was 1466.67, 1923.33 and 1573.33 for control, treatment 1 and treatment 2 correspondingly. Average feed intake was control (94.60), T1(97.31) and T2(97.54) correspondingly. The feed conversion ratio for the control, treatment 1 and treatment 2 were 6.06, 5.18 and 6.49, respectively. The present result may enable the farmers to minimize the feed cost and increase the quality of the growth performance.